Pengaruh Proses Belajar Mengajar Yang Menggunakan Dan Tidak Menggunakan Alat Peraga - Beny Suyanto; Karno .; Sujangi . (GEMA LINGKUNGAN KESEHATAN, 2015)
ater treatment props used in the learning process is intended to clarify the material presented lectures more interesting and easier to understand. How much influence the process of learning to use and not use props is a water treatment in this study.Analytical study of the design of one group pretest-posttest conducted with a sample of Environmental Health Prodi third semester students during the academic year 2014/2015 in themonth of September until November 2014. Students of 51 people divided into two groups A and group B were based on the averagevalue of the first semester GPA (a) and II (two) are intended to have the same ability level andevenly. Group learning process does not use props and group B with the use of props watertreatment. The results of students' pre-test group A and B do not pass the value of the gain and thehighest and lowest 50 20. While the results of a group of students posttest score average of 67.3, the lowest and highest value of 60.7 79.3. The student group B average value 78.3, the lowest value of 70, and the highest 84.7. There are significant differences utilize the learning process and not use props.The above data indicate that the level of understanding of the students in the lecture using props are better than without props. Konfrehensif cognitive abilities and effective student group Bwas also better. Props water treatment also allows professors to teach and improve communication skills for students. Thus, each subject-oriented knowledge and skills needed innovation of scienceand technology major props adequate.